1958
DOI: 10.1002/hlca.660410120
|View full text |Cite
|
Sign up to set email alerts
|

Zur Kenntnis der Pseudojononsynthese nach Kimel & Sax

Abstract: In the synthesis of pseudoionone by pyrolysis of dehydro‐linalyl‐acetoacetate (Kimel & Sax, US‐Pat. 2 661 368) an isomeric ketone is formed, the structure of which has been elucidated by degradation to d,l‐puleganic acid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

1958
1958
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…With the exception of diastereosel ective examples,9,10 for axially chiral allenyl halides such as 2 , the level of enantiomeric enrichment was at best modest even when employing known conditions starting from mesylation of optically pure propargyl alcohols (R) - 1 and (S)- 1 1,2,11,12. Our interest13 in both the Saucy-Marbet rearrangement for the synthesis of chiral allenes9,14–16 and reactivities of alkynyl halides such as 5 17,18 prompted us to explore the synthesis of en antiomerically pure allenyl halides 7 by uniting the two concepts 19. We communicate here the concept of employing a stereospecific Saucy-Marbet rearrangement of alkynyl halides in the synthesis of highly enantiomerically enriched allenyl halides.…”
mentioning
confidence: 99%
“…With the exception of diastereosel ective examples,9,10 for axially chiral allenyl halides such as 2 , the level of enantiomeric enrichment was at best modest even when employing known conditions starting from mesylation of optically pure propargyl alcohols (R) - 1 and (S)- 1 1,2,11,12. Our interest13 in both the Saucy-Marbet rearrangement for the synthesis of chiral allenes9,14–16 and reactivities of alkynyl halides such as 5 17,18 prompted us to explore the synthesis of en antiomerically pure allenyl halides 7 by uniting the two concepts 19. We communicate here the concept of employing a stereospecific Saucy-Marbet rearrangement of alkynyl halides in the synthesis of highly enantiomerically enriched allenyl halides.…”
mentioning
confidence: 99%
“…Ynamides are becoming attractive building blocks in organic synthesis. We have been investigating reactivities of ynamides 12-15 and have demonstrated that chiral ynamides are useful in a stereoselective Ficini−Eschenmoser−Claisen rearrangement. , Given the power of the [3,3]-sigmatropic rearrangement in organic synthesis, we explored the utility of ynamides 1 in a stereoselective Saucy−Marbet rearrangement, an appealing entry to chiral allenes (Figure ). Although Saucy and Marbet 18a first reported the utility of propargyl alcohols in Claisen-type rearrangements in 1958, there was just one account 19 describing stereochemical issues surrounding this rearrangement using optically enriched propargyl alcohols.…”
mentioning
confidence: 99%
“…We quickly established the feasibility of Saucy−Marbet rearrangement using chiral ynamides (Scheme ) . Reactions of ynamide 7 with ( S )- and ( R )- 8 using PNBSA at 100 °C gave allenes 9 22 and 10 in 55 and 51% yields, respectively, as single diastereomers, suggesting excellent chirality transfer from chiral alcohols to the allenic axial center. 18d,
1
…”
mentioning
confidence: 99%
“…This research was later expanded upon with the first example of a Saucy-Marbet139 rearrangement of chiral ynamides with chiral propargyl alcohols140 (Scheme 145). After addition of the alcohol to give either 548 (matched) or 550a (mismatched), the resulting yne-enamides undergo a concerted [3,3]-sigmatropic rearrangement.…”
Section: Reactions Of Ynamidesmentioning
confidence: 99%